Magnitude and determinants of multimorbidity and health care utilization among patients attending public versus private primary care: a cross-sectional study from Odisha, India - Sanghamitra Pati; Subhashisa Swain; J. André Knottnerus; Job F. M. Metsemakers; Marjan van den Akker (BMC, 2020)
Abstract Background Multimorbidity in primary care is a challenge not only for developing countries but also for low and medium income countries (LMIC). Health services in LMIC countries are being provided by both public and private health care providers. However, a critical knowledge gap exists on understanding the true extent of multimorbidity in both types of primary care settings. Methods We undertook a study to identify multimorbidity prevalence and healthcare utilization among both public and private primary care attendees in Odisha state of India. A total of 1649 patients attending 40 primary care facilities were interviewed using a structured multimorbidity assessment questionnaire collecting information on 22 chronic diseases, medication use, number of hospitalization and number of outpatient visits. Result The overall prevalence of multimorbidity was 28.3% and nearly one third of patients of public facilities and one fourth from private facilities had multimorbidity. Leading diseases among patients visiting public facilities included acid peptic diseases, arthritis and chronic back pain. No significant difference in reporting of hypertension and diabetes across the facilities was seen. Besides age, predictors of multimorbidity among patients attending public facilities were, females [AOR: 1.6; 95% CI 1.1-1.3] and non-aboriginal groups [AOR: 1.6; 95%CI 1.1-2.3] whereas, in private females [AOR: 1.6; 95%CI 1.1-2.4], better socioeconomic conditions [AOR 1.4; 95% CI 1.0-2.1] and higher educational status [primary school completed [AOR 2.6; 95%CI 1.6-4.2] and secondary schooling and above [AOR 2.0; 95%CI 1.1-3.6] with reference to no education were seen to be the determinants of multimorbidity. Increased number of hospital visits to public facilities were higher among lower educational status patients [IRR: 1.57; 95% CI 1.13-2.18] whereas, among private patients, the mean number of hospital visits was 1.70 times more in higher educational status [IRR: 1.70; 95%CI 1.01-3.69]. The mean number of medicines taken per day was higher among patients attending private hospitals. Conclusion Our findings suggest that, multimorbidity is being more reported in public primary care facilities. The pattern and health care utilization in both types of settings are different. A comprehensive care approach must be designed for private care providers.